Dampak Pengajian Kitab Minhajul Muta’alim dalam Meningkatkan Wirausaha Masyarakat Lokal di Desa Banjaranyar - Erly Juliyani (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
This study aims to examine the influence of Minhajul Muta'alim religious study activities held during the month of Ramadan on the development of community entrepreneurship in Banjaranyar Village. Minhajul Muta'alim is a classic reference in Islamic boarding school education that emphasizes values ​​such as honesty, independence, hard work, and blessings in seeking knowledge and sustenance. This study uses a descriptive qualitative approach. The results show that religious study activities during the month of Ramadan have a positive impact on community economic activities, especially in the food and beverage trade sector which is busy before and after the religious study time. The values ​​taught in the book encourage the emergence of an entrepreneurial spirit based on Islamic ethics, such as honesty in transactions, seeking halal sustenance, and making business part of worship. Furthermore, social interactions between students and local traders contribute to strengthening the village's economic network and increasing social solidarity among residents. In this context, Islamic boarding schools serve as spiritual centers that provide motivation and moral values ​​to the community, rather than as direct economic actors. Therefore, it can be concluded that Minhajul Muta'alim recitation plays a strategic role in shaping the entrepreneurial mindset of village residents, who are religious, independent, and oriented toward blessings. This study recommends that similar activities can be used as a strategy for community economic empowerment based on Islamic values.